2018
DOI: 10.1097/md.0000000000010431
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin in the treatment of hepatorenal syndrome

Abstract: Background:Hepatorenal syndrome is a fatal complication of advanced cirrhosis. Terlipressin is the most widely used treatment method, however, the therapy effects remain inconsonant. We aim to systematically assess the safety and efficacy of terlipressin for hepatorenal syndrome.Methods:We conducted a systematic review and meta-analysis. Randomized controlled trials involving terlipressin for hepatorenal syndrome were included in a systematic literature search. Two authors independently assessed the studies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
2
62
0
2
Order By: Relevance
“…Several meta-analyses comparing vasopressin and norepinephrine in critical care units have been reported. [36][37][38] Wang et al administered vasopressin and norepinephrine to patients with hepatorenal syndrome and compared recovery rates from this syndrome. They concluded that the rate of recovery was equivalent for vasopressin and norepinephrine (odds ratio = 1.01, 95% CI: 0.65-1.57, p = 0.96).…”
Section: Explanation Of Resultsmentioning
confidence: 99%
“…Several meta-analyses comparing vasopressin and norepinephrine in critical care units have been reported. [36][37][38] Wang et al administered vasopressin and norepinephrine to patients with hepatorenal syndrome and compared recovery rates from this syndrome. They concluded that the rate of recovery was equivalent for vasopressin and norepinephrine (odds ratio = 1.01, 95% CI: 0.65-1.57, p = 0.96).…”
Section: Explanation Of Resultsmentioning
confidence: 99%
“…Considering the fact that artificial colloid Haemaccel was used instead of albumin, the difference in outcome in terms of full recovery can be justified. The expensive treatment and non-compliant patients with regard to follow-up were the limitations faced during the study [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the presence of unusual amino acids such as Dha and the formation of the thioether bond between Dha and Cys in vasopressin could prevent cleavage, an extra Gly was always placed between the engineered cleavage site and the vasopressin sequence. The presence of N-terminal amino acids or other chemical substituents in vasopressin sequence has rendered active molecules such as terlipressin, with three glycines in this position, which is marketed for clinical use (Dobre et al, 2011; Wang et al, 2018). Thus, the presence of glycine or other amino acids at this position is tolerated in terms of activity and enables easier cleavage.…”
Section: Discussionmentioning
confidence: 99%